A note on invariance principles for v. Mises' statistics - Denker, Manfred; Keller, Gerhard; Grillenberger, Christian (Metrika, 1985)
We extend Filippova's result on weak convergence of v. Mises' functionals and prove a weak invariance principle. Applications toU-statistics are given and extensions to contiguity and weakly dependent processes are briefly discussed.